BOOK REVIEW - IPS, Editor (Indian Phytopathology, 2002)
Tropical Mycology : (Editors: K.K. Janardhanan, C. Rajendran, K. Natarajan and D.L. Hawksworth), 1997, 315 pages, illustrated, (ISBN 81-204-1117-X), Oxford and IBH Publishing Co. Pvt. Ltd., New Delhi, Rs. 650/- (for south Asia only).